Application of neural networks to the analysis of consumer opinions - Mysan, Roman; Loichuk, Ivan; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2019)
This paper presents an analysis of the possibilities of using neural networks to classify text data in the form of comments. Moreover, results of research of two neural network optimization methods: Adam and Gradient are presented. The aim of the work is to conduct research on the behavior of the neural network depending on the change of parameters and the amount of data used to teach the neural network. To achieve the goal, a test application was created. It uses a neural network to display the overall assessment of the accommodation facility based on the added user feedback.